Review paperSepsis and septic encephalopathy: characteristics and experimental models - Ziaja, Marek (Folia Neuropathologica, 2012)
The inflammation is a response of the organism to damaging factors and leads to the limitation of the tissue destruction. During the inflammatory process, there is stimulation of the immune system as well as other tissue cells. However, sometimes this reaction is excessive and can bring to the sepsis and development of multiorgan insufficiency. Phenomena observed during sepsis influence also, directly or indirectly on the nervous system and cause septic encephalopathy (SE) with consciousness and cognitive functions loss and other neurological symptoms. Often it can lead to persistent brain injuries, and almost always cause changes, which can be manifested later, even many years after the sepsis. It is supposed that in many cases, septic encephalopathy can be the main reason of death during sepsis. Still increasing concern of SE brought to the development of several animal models of this syndrome, which made possible detailed recognition of phenomena accompanying of septic encephalopathy. They include direct administration of endotoxins, or surgical intervention within the abdominal cavity. Every presented experimental model has advantages and weakness, but they make possible the modeling of the inflammatory reaction and multidirectional examining of accompanying phenomena.